Judge-Dependence in Degree Constructions. (1st October 2016) - Bylinina, Lisa
Abstract: The article discusses judge-dependence of gradable adjectives and degree constructions. Take the positive construction: whether sentences 'John is tall', 'This cake is tasty', or 'Mary is smart' are true or false depends not only on a state of affairs but also on whose opinion is being expressed. At the same time, the adjectives appearing in these subjective statements differ in ways that are often considered crucial for shaping an analysis of judge-dependence. Consider embedding under 'find' and the ability to take overt 'judge'-phrases: (1) I find this cake tastier than that one / John smarter than Mary / *Mary taller than John. (2) Apples are tasty / ??John is tall / ??Mary is smart (?)for / to me. To explain these patterns, I look at different classes of subjective lexical items, limiting myself to the domain of degree constructions. I take predicates of personal taste (PPTs) like 'tasty' or 'fun' as a starting point, as they have received the most attention in the literature and are usually taken to be representative of the whole class of subjective predicates. A closer cross-linguistic look at more items like positive dimensional adjectives ('tall'), evaluative adjectives ('smart'), extreme adjectives ('gigantic') and modal degree morphemes like 'too' shows that, for most cases, there is no evidence for a judge argument, quite often associated with subjectivity across the board. At the same time, I argue that postulating a judge argument for 'tasty' or 'fun' and capturing judge-dependence of the other classes with a judge index of evaluation—'two types of subjectivity' view—is not a good solution as well. Taking an intuition that the extra argument of PPTs is an Experiencer rather than the judge seriously, I observe that, indeed, the presence of an extra argument correlates with reference to an experience event being part of the predicate semantics. On top of that, I show that the PPT Experiencer argument does not show any special judge-dependent behaviour that is not observed for other Experiencers in different constructions. In a nutshell, I adopt a judge index of evaluation account of subjectivity (Lasersohn 2005, 2009 ), but the role that I assume for the overt 'judge'-phrases is different from what Lasersohn suggests. For me, these 'judge' PPs are not index shifters, but are Experiencer arguments of PPT predicates. Finally, I motivate and formulate a general principle regulating who can make a direct assertion about someone's internal state ('Judge=Experiencer' principle).